Sudden Stops and Financial Frictions : Evidence from Industry Level Data - Cowan, Kevin (2012)
The nature of the microeconomic frictions that transform sudden stops in output collapses is not only of academic interest, but also crucial for the correct design of policy responses to prevent and address these episodes and the lack of evidence on this regard is an important shortcoming. This paper uses industry-level data in a sample of 45 developed and emerging countries and a differences-in-differences methodology to provide evidence of the role of financial frictions for the consequences of sudden stops. The results show that, consistently with financial frictions being important, industries that are more dependent on external finance decline significantly more during a sudden stop, especially in less financially developed countries. The results are robust to controlling for other possible mechanisms, including labor market frictions. The paper also provides results on the role of comparative advantage during sudden stops and on the usefulness of various policy responses to attenuate the consequences of these shocks.